A rare case of oral pemphigus vulgaris in teenager suspected induced by stress - Dewi Kania Intan Permatasari (Journal of Dentomaxillofacial Science, 2021)
AbstractObjective : To provide early therapy in teenager pemphigus vulgaris patients so that healing of lesions in the oral cavity is faster.Methods : A 14-year-old boy came to the oral medicine installation RSGM Unpad with complaints of canker sores since 5 days before, initially only at buccal mucosa and treated but multiplied and getting worse. Ulsers like this is the first time experienced by patient. The patient is on antibiotic therapy and is undergoing a national examination. Extra oral examination found dry upper and lower lip, exfoliative and bleeding tendency. Intra-oral examination found ulcer lesions covered with sloughing on the upper and lower labial mucosa, right and left buccal mucosa, and tongue. The dorsum of the tongue has a yellowish white plaque that can be scrapped and does not leave the erythema area. The results of laboratory tests showed an increase in leukocytes, platelets and LEDs while total Ig E was normal. Based on the anamnesis and clinical examination, we diagnosed patient with pemphigus vulgaris. Patient get non-pharmacological therapy, namely oral hygiene instructions (OHI), communication, information, and education (CIE) while pharmacological therapy in the form of dexamethasone, prednisone, vitamin B12 and hyaluronic acid.Results : One month after treatment, the lesions have healed.Conclusion : Appropriate early therapy, good communication, information and education about the lesions in patient with oral pemphigus vulgaris will Â relieve stress Â and accelerate the process of healing lesions, especially in teenager patient.Keywords : Oral pemphigus vulgaris, stress, teenager